2015
DOI: 10.1039/c5pp00156k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of N-retinylidene-N-retinylethanolamine (A2E) levels in central and peripheral areas of human retinal pigment epithelium

Abstract: SUMMARY The bis-retinoid N-retinylidene-N-retinylethanolamine (A2E) is one of the major components of lipofuscin, a fluorescent material that accumulates with age in the lysosomes of the retinal pigment epithelium (RPE) of the human eye. Lipofuscin, as well as A2E, exhibit a range of cytotoxic properties, which are thought to contribute to the pathogenesis of degenerative diseases of the retina such as Age-related Macular Degeneration. Consistent with such a pathogenic role, high levels of lipofuscin fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Mass spectrometric and chromatographic analysis of normal human and monkey eyes revealed that the well-studied lipofuscin component A2E and its major oxidation products are lower in macula than in periphery. 100103 Thus, the relevance of experimental A2E loading of cultured RPE cells to achieve AMD milestones such as cell death 104 and complement dysregulation 105 can be questioned. Because the lipofuscin phototoxicity hypothesis underlies use of visual cycle modulators for AMD 106 and blue- light blocking intraocular lenses for cataract, 107, 108 our conclusions if sustained could have wide-ranging impact on therapeutic strategies for age-related eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometric and chromatographic analysis of normal human and monkey eyes revealed that the well-studied lipofuscin component A2E and its major oxidation products are lower in macula than in periphery. 100103 Thus, the relevance of experimental A2E loading of cultured RPE cells to achieve AMD milestones such as cell death 104 and complement dysregulation 105 can be questioned. Because the lipofuscin phototoxicity hypothesis underlies use of visual cycle modulators for AMD 106 and blue- light blocking intraocular lenses for cataract, 107, 108 our conclusions if sustained could have wide-ranging impact on therapeutic strategies for age-related eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence which suggests that the link between lipofuscin accumulation in the RPE and AMD progression is more tenuous. Although A2E is known to be produced in the RPE, it has been shown that, in humans, A2E is preferentially located in the RPE cells of the peripheral retina, rather than the central area of the retina containing the macula [57]. Therefore, in fundus autofluorescence (FAF) imaging, the higher levels of lipofuscin fluorescence associated with the central area of the RPE cannot be exclusively attributed to the concentration of A2E.…”
Section: Metabolic Processes In the Posterior Eyementioning
confidence: 99%
“…The main fluorophores responsible for FAF imaging are visual cycle byproducts of the bisretinoid family that originate in photoreceptor outer segments and enter RPE via daily phagocytosis 7,12. N-retinylidene-N-retinylethanolamine (AE2) is one prominently investigated molecule13 recently shown to be abundant in peripheral retina1419; bisretinoid discovery and characterization are ongoing 20…”
mentioning
confidence: 99%